Comparison of laparoscopic pyeloplasty vs. robot-assisted pyeloplasty for the management of ureteropelvic junction obstruction in children - Pérez-Marchán, Marcos; Pérez-Brayfield, Marcos (Frontiers in Pediatrics, 2022)
Background Ureteropelvic junction obstruction (UPJO) is a commonly observed abnormality in pediatric urology. Minimally invasive approaches have gained popularity in recent years. Studies have demonstrated excellent results with both laparoscopic pyeloplasty (LAP) and robot-assisted pyeloplasty (RAP). Few studies have compared the experience of both procedures performed in a single institution. Our objective is to compare laparoscopic pyeloplasty and robot-assisted pyeloplasty in the Puerto Rican pediatric population. Methods We conducted a retrospective cohort study using our clinic's database on patients with UPJO that were operated by the same surgeon (MPB) from 2008 to 2019. Statistical analysis was conducted of demographics, preoperative studies, perioperative data and complications of both procedures. This study was approved by our local IRB committee. Results A total of 86 patients that underwent pyeloplasty with at least 3 years of follow up were recorded for this study. Laparoscopic pyeloplasty and robot-assisted pyeloplasty were performed in 44 (51.1%) and 42 (48.8%) patients, respectively. Patient age ranged between 4 months and 17 years (LAP group - mean age of 6.19 years/RAP group - mean age of 7.07 years). Success rates was high in this series (LAP - 100% and RAP −95%). Using Wilcoxon signed rank test and Mann whitney sum test, significant differences between preoperative and postoperative hydronephrosis grading were observed in both LAP and RAP groups. However, no significant difference was seen regarding reduction of hydronephrosis grading when comparing both groups. No intraoperative complications were seen on either group. Conclusion Both LAP and RAP are safe and effective procedures that can properly manage UPJO. Our study shows that, under experienced hands, pure laparoscopic pyeloplasty achieves comparable results to robotic assisted laparoscopic pyeloplasty. Pediatric urologists should be comfortable offering either of these approaches as they demonstrate high success rates in our pediatric population. Selection of LAP vs. RAP approach depends on the Surgeon's preference or experience, and on institutional availability. Minimally invasive therapies will continue to gain popularity with future advances in laparoscopic and robotic technology.